Analyzing EEG Signals with Machine Learning for Diagnosing Alzheimer’s Disease - Podgorelec, V. (Elektronika ir Elektrotechnika, 2012)
In order to have the greatest treatment impact the early and accurate diagnose of Alzheimer’s disease (AD) is essential. In this paper we present a method for analyzing EEG signals with machine learning approach in order to diagnose AD. We show how to extract features out of EEG recordings to be used with a machine learning algorithm for the induction of AD classification model. The obtained results are very promising. DOI: http://dx.doi.org/10.5755/j01.eee.18.8.2627